INTEGRASI TEKNOLOGI DAN MANAJEMEN INOVASI PEMBELAJARAN - Puput Puspito Rini (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
The integration of technology in education is a multidimensional transformation that includes the use of digital devices, the development of technology-based curriculum, to organizational innovation driven by artificial intelligence and the Internet of Things in the modern era. This research aims to examine the relationship between technology integration and learning innovation management through a systematic analysis of various models, strategies, and ecosystems that support its implementation, including pedagogical frameworks, leadership, and cross-sectoral implications in a comprehensive manner. The method used is Systematic Literature Review (SLR) with a transparent and structured procedure, including the formulation of research questions, the preparation of search strategies, the determination of inclusion-exclusion criteria, and selection documentation using PRISMA Diagram Flow. The research findings identify four main categories, namely: technology integration models and frameworks in learning using TPACK and SAMR, pedagogical innovation and technology-based curriculum development, leadership, organization, and innovation and technology ecosystems, innovation management, and sustainability across industry and environmental sectors. The research concludes that the success of technology integration is determined by a strong pedagogical framework, educators' digital competence, collaborative instructional leadership, and internal governance that is oriented towards long-term sustainability, resulting in adaptive, competitive, and resilient management of learning innovations in the digital age.